A cartografia escolar na produção acadêmica em geografia e educação: uma análise das pesquisas brasileiras realizadas entre 1995 e 2020 - Castanha, Rafael da Silva (2023)
In this dissertation, we conducted a research categorized as state of the art, which included the survey and classification of works on School Cartography produced by postgraduate programs (stricto sensu) in Geography and Education in Brazil, between 1995 and 2020. This is an investigation developed through the quantitative methodology of a descriptive nature, supported by the use of descriptors and filters available in the CAPES Catalog of Theses and Dissertations. Through this, we seek to present a historical overview of the set of production in School Cartography, according to the respective thematic axes disseminated in the Brazilian context, since the consolidation of this area of ​​research as an academic field, with the first colloquia on cartography for children and schoolchildren held by several universities in the country. The theoretical basis was based on the contributions of the main authors and reference authors in the areas of Education, School Geography and School Cartography. Among the main conclusions of this study, we highlight that School Cartography has gained greater notoriety in the academic field, as productions become more dynamic and aim to understand the processes of reading and representing space in the school environment, from different perspectives and theoretical methodological analyses. However, it was also possible to verify that research in School Cartography, both in the area of ​​Geography and Education, is still intensely concentrated mainly in universities in the Southeast, South and Central-West of the country, while in the other regions, productions are scarce or even non-existent.